Maligned presidents : the late 19th century - Skidmore, Max J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Certain 19th Century presidencies contrast common perceptions of the office's authority and strength. These presidents were a strong group and were anything but insignificant. They fought substantial battles with Congress, and often won. This book seeks to provide more substantive analysis of maligned presidencies, and the legacies left behind.
Keywords: Science; Science; Science, general